SOCIO-DIFFERENTIAL CHARACTERISTICS OF THE THINKING OF MODERN YOUTH AND THEIR PHILOSOPHICAL AND PEDAGOGICAL ANALYSIS (TAMADDUN NURI JURNALI, 2024)
This article analyzes the social differential characteristics of the thinking of modern student youth. It examines the differences in the thinking of students from various social strata and how these differences manifest in the educational process. In particular, the article investigates how students' thinking is shaped and transformed in relation to socio-cultural, economic, and other social factors. From a philosophical-pedagogical perspective, it discusses the formation of social thinking, its education, and the role of self-awareness in students.